A Combination of Fuzzy AHP and TOPSIS Method for the Supplier Selection Problem (Case Study: Advertising Company) - Mohammad Ali Beheshtinia; Vahid Nemati-Abozar (مجله مدل سازی در مهندسی, 2017)
One of the most important aspects of designing a supply chain is the matter of supplier selection. Itâs a complicated issue because suppliers should satisfy some criteria and ranking those leads to a MCDM problem. Therefore, a structured and systematic approach is required to solve this problem. In this article, we address supplier selection problem in advertising industry and propose two new criteria. Correspondingly, in order to evaluate suppliers in the industry a hybrid approach is proposed which combines fuzzy AHP with fuzzy TOPSIS techniques. Each method has its cons and pros we try to use the advantages of the both methods in the proposed hybrid approach. On the other hand, the related parameters in this decision making problem are qualitative. Some errors could happen in transformation of the qualitative parameters to quantitative ones. Accordingly, in transforming procedure we use fuzzy theory to reduce these errors.